2021
DOI: 10.1053/j.gastro.2021.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Simple Sugar and Sugar-Sweetened Beverage Intake During Adolescence and Risk of Colorectal Cancer Precursors

Abstract: BACKGROUND & AIMS: Recent increasing trends in earlyonset colorectal cancer (CRC) strongly supports that early-life diet is involved in CRC development. However, data are lacking on the relationship with high sugar intake during early life. METHODS:We prospectively investigated the association of adolescent simple sugar (fructose, glucose, added sugar, total sugar) and sugar-sweetened beverage (SSB) intake with CRC precursor risk in 33,106 participants of the Nurses' Health Study II who provided adolescent die… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 50 publications
3
55
0
1
Order By: Relevance
“…Of the ten studies included, five were prospective cohort studies ( 20 24 ) and five were a case-control studies ( 25 – 29 ). Four studies examined the relationship between early onset colorectal adenomas ( Table 2 ) and potential risk factors, including diet ( 20 – 23 ) and six examined risk factors, including diet, for developing early onset colorectal cancer ( 24 – 29 ) ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the ten studies included, five were prospective cohort studies ( 20 24 ) and five were a case-control studies ( 25 – 29 ). Four studies examined the relationship between early onset colorectal adenomas ( Table 2 ) and potential risk factors, including diet ( 20 – 23 ) and six examined risk factors, including diet, for developing early onset colorectal cancer ( 24 – 29 ) ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…9 The authors found that, regardless of dietary patterns in adulthood, fructose consumption during adolescence was statistically significantly associated with risk of early-onset rectal adenoma and high-risk adenoma (per 5% increase in calories per day). 5 Similarly, there was an elevated but not statistically significant association between SSB consumption during adolescence and risk of early-onset rectal adenoma (per 1 serving/day increase). These findings might partly explain increasing incidence rates of early-onset CRC, although the modest effect sizes (adjusted odds ratios ranging from 1.25 to 2.23) correspond to population attributable fractions of 10%-20%.…”
mentioning
confidence: 92%
“…2,3 Higher incidence rates of early-onset CRC observed among those born in and after the 1950s and 1960s suggest risk factors in early life (eg, childhood and adolescence) play an important role. 1,4 In this issue of Gastroenterology, Joh et al 5 examine the association between consumption of fructose and sugarsweetened beverages (SSBs) during adolescence and risk of colorectal neoplasia (ie, total adenoma, proximal adenoma, rectal adenoma, and high-risk adenoma), particularly early-onset (younger than 50 years), in women participating in the Nurses' Health Study II. 5 Consumption of simple sugars, particularly fructose, has paralleled increasing incidence rates of early-onset CRC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies revealed that early-onset CRC is related to prolonged sedentary television viewing time, a surrogate for a sedentary lifestyle, and adolescent simple sugar and sugarsweetened beverage intake was associated with a higher risk of colorectal neoplasms. 19,20…”
mentioning
confidence: 99%